Efektivitas Penggunaan Berbagai Jenis Pupuk Kompos terhadap Pertumbuhan dan Produksi Tanaman Terung (Solanum melongena, L.) - Yeni Kartika; Rosmaiti Rosmaiti; Syukri Syukri (Tumbuhan : Publikasi Ilmu Sosiologi Pertanian Dan Ilmu Kehutanan, 2024)
One of the most profitable agricultural commodities is eggplant. Eggplants also need to be large enough to be eaten as vegetables or vegetables. Eggplant farmers in Indonesia often experience crop failure problems due to excessive use of chemical fertilizers, which make the soil acidic and harmful to the environment. Efforts to help the growth and development of eggplants by using compost. The focus of the research is to determine the effectiveness of various compost fertilizers on the growth and production of eggplant plants. It was carried out from July-September 2023 in Sidorejo Village, Langsa Lama District, Langsa City. In this study, a Non-Factorial Group Random Design (RAK) was used. The observed factor is various compost fertilizers, which consist of 11 composts with 1 variety of Mustang F1 eggplant which is repeated 3 times. The results showed that the treatment of various types of compost fertilizers had a real effect on the plant height parameters of 15 HST and stem diameter of 45 HST. However, it had an insignificant effect on the parameters of average fruit weight, fruit weight, number of fruit planted, average fruit size and production per hectare at harvest time. The benefits of this research are improving the quality of soil fertility, plants becoming fertile, and improving plant quality and productivity. The best result was obtained from K8 (gamal leaf compost), but it was as good as K7 (petai leaf compost). The application of compost fertilizer is effective for all parameters of eggplant plants, except for the treatment of K5 (bagasse compost) because the average value is below 100%, the most effective compost fertilizer is obtained in the treatment of K8 (gamal leaf compost), but it is as good as K4 (straw compost) and K7 (petai leaf compost). To cultivate eggplant plants, it is recommended to use gamal leaf compost, straw compost, petai leaf compost.